A preliminary investigation into the suitability of Kawui wood (Vernonia arborea) for pulp and paper. (2nd July 2020) - Indrayanti, Lies; Siska, Grace; Wardhani, I. Y.
ABSTRACT: The anatomical and chemical properties of a lesser known species, Kawui wood, were investigated Two trees were examined based on IAWA, ASTM and SNI. A completely randomised design was used with radial direction of the trunk (sapwood and heartwood) as the factor, in three replications. It indicated the highest to lowest cell proportions are fibres, rays, vessels and parenchyma. The highest proportion of rays was in the sapwood, while the fibre was in the heartwood. However, the average fibre length in the sapwood was higher than the heartwood, while the lumen diameter showed the reverse. Holocellulose, α-cellulose, lignin, extractives, and ash content of the sapwood was higher than the heartwood. Based on its anatomical and chemical properties, Kawui wood can be included in grade II–IV, which is suitable for medium quality pulp and paper production.